PERLINDUNGAN HUKUM TERHADAP HAK ATAS INFORMASI KONSUMEN JUAL BELI ONLINE DITINJAU BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Andi Nurfadhila Brilyana Baso; Asnawi Asnawi; Aris Setyanto Pramono (Res Justitia : Jurnal Ilmu Hukum, 2023)
The development of the world in the modern era is increasingly widespread economic activity by utilizing the Internet as a medium of communication in electronic commerce or e-commerce as a medium of transaction. Every consumer according to Article 4 letter c of the Consumer Protection Act has the right to correct, clear and honest information. So information is an important thing for consumers, if the information is not conveyed correctly it is a violation by business actors against consumers. This research method is research using a statutory approach and a conceptual approach. Data collection techniques were carried out by means of literature studies and interviews. The primary data used is interviews with consumers who have experienced losses in online buying and selling transactions, while the secondary data used is Law Number 8 of 1999 concerning Consumer Protection, Law Number 11 of 2008 and the Civil Code. Based on the results of the research, referring to article 4, article 7 of the Consumer Protection Act and article 9 of Law Number 11 of 2008 concerning Information and Electronic Transactions that the granting of the right to information for consumers is an important element in consumer rights. Thus, legal protection of the right to consumer information has not been able to work properly because business actors are still ignoring their obligations and the lack of concern for business actors which results in non-fulfillment of guarantees for consumer rights